2021
DOI: 10.1016/j.ijid.2021.08.035
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 diagnosis using dried blood spots from patients in Kinshasa, DRC: a tool to detect misdiagnosis and achieve World Health Organization 2030 targets

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Our pilot study provides pioneer data related to the seroprotection to six infectious diseases preventable by vaccination in a cohort of children and adolescents living in Kinshasa (DRC) using samples collected during 2016–2018. The quantification of IgG levels in DBS did not present any difficulty compared to plasma, and we detected IgG in the plasma fraction present in the dried blood drop collected on Whatman paper, as we previously did for other pathogens 20 , 21 , 25 27 .…”
Section: Discussionsupporting
confidence: 73%
“…Our pilot study provides pioneer data related to the seroprotection to six infectious diseases preventable by vaccination in a cohort of children and adolescents living in Kinshasa (DRC) using samples collected during 2016–2018. The quantification of IgG levels in DBS did not present any difficulty compared to plasma, and we detected IgG in the plasma fraction present in the dried blood drop collected on Whatman paper, as we previously did for other pathogens 20 , 21 , 25 27 .…”
Section: Discussionsupporting
confidence: 73%
“…It is also applicable to many other regions in Europe with similar challenges in health care outreach to the population. The use of capillary blood sampling for large-scale serological studies is not limited to SARS-CoV-2 S protein, and the feasibility of the strategy for detection of antibodies to other antigens has previously been demonstrated [26,[32][33][34]. It is easy to envision a comprehensible national surveillance system of vaccine effectiveness, especially focussed upon populations that receive care outside of centralised hospital facilities, such as vulnerable and frail individuals at nursing homes or long-term care facilities.…”
Section: Discussionmentioning
confidence: 99%
“…This is considerably lower compared to performance reported by others using DBS. In a study conducted among PLWH on ART in Kinshasa, Democratic Republic of Congo Barquín et al 12 reported a sensitivity of 100% (95% CI 98.6%, 100%) and specificity of 100% (95% CI 96.0%, 100%) for the VIDAS HIV Duo Quick. Differences in performance between our study and Barquín et al .…”
Section: Discussionmentioning
confidence: 99%